Fostering Pancasila Awareness: Youth Dialogue to Counter the Threat of Global Radicalism - Muhammad Yusuf Rambe; Deny Hadi Siswanto; Helena Anggraeni Putri; Kintoko Kintoko (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The primary objective of this activity was to enhance students' understanding of the critical importance of instilling and practicing the values of Pancasila as a means to confront the growing threat of radicalism in the era of globalization. This event was conducted at Muhammadiyah Seyegan Vocational School and engaged 25 twelfth-grade students in a dynamic and interactive dialogue session. The program featured a knowledgeable resource person who delivered an in-depth presentation on a specific theme, which was followed by an engaging discussion to explore and reflect upon the key points shared. The outcomes of the dialogue revealed that the values embedded within Pancasila are not only foundational but also remain highly relevant and applicable in addressing contemporary challenges. This initiative sought to provide students with a clearer understanding of Pancasila as a comprehensive national worldview, a philosophical cornerstone of Indonesia, and a guiding principle for governance and citizenship. Beyond theoretical understanding, the activity encouraged participants to internalize Pancasila's principles in their daily interactions and decisions, fostering a commitment to embody these values in their personal lives, within their families, in community settings, and in their contributions to national and state affairs. Through this approach, the program aimed to cultivate a sense of responsibility and pride in upholding Pancasila as a unifying and protective force against radicalism